Unexpected Consequences of Ricardian Expectations - Erratum - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
This note identifies a severe mistake in my article “Unexpected Consequences of Ricardian Expectations” that appeard in this journal in the July 2013 issue.
urn:nbn:de:bvb:19-epub-17249-7
Keywords: E2; E12; E6; H6; 330; Barro-Ricardo equivalence; Ricardian equivalence; fiscal policy; debt; taxation; rational expectations; Ricardian expectations; Barro expectations; tax neutrality